The World of Bees : SUPER MI DISCOVERY - Mia, Cee, Cee; Lecomte, Julie; Wan-Lau, Ruth (Singapore : WS Education, 2023)
"Come discover with me, Super Mi! How many oceans does Earth have? What is going on underneath the waters? My name is Mi and though I'm still small, the world has no more secrets from me anymore! That's because of my superpowers. As Super Mi, I can discover everything I want to know! Discover, experiment and learn with the little scientists! Each little scientist has something new to teach readers. Through engaging narratives and full-colour illustrations, I'm a Little Scientist! introduces children to the exciting and ever-advancing world of science. Everyone can be a little scientist!"--
First published in French under title: Super Mi, En route chez les abeilles
Translated from the French
Keywords: Science -- Juvenile literature; Bees -- Juvenile literature